"Siedem ksiąg" żywieckiego cechu krawieckiego z 1745 roku = "The seven books" of the Żywiec tailors` guild from 1745 - Dusik, Jarosław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Żywiec was founded at the turn of the 13th and 14th centuries. As the only urban center in the area, it had a well-developed craft guild system. One of the oldest guilds in Żywiec was the tailors` guild, which, for over 100 years (1580-1699), formed a joint association with furriers. After its dissolution, the tailors began to strengthen their independent image.
Keywords: guilds; tailor`s guild; guild master; tailors; crafts; cech; cech krawiecki; cechmistrz; krawiec; rzemiosło